Simulation of transmission line matching networks in GaAs MMIC applications - Monsod, Trevor Andrei Free A.
Monolithic microwave integrated circuits (MMICs) are widely used today due to their high frequency applications and small size. The matching networks used for these circuits are essential for the MMIC applications to perform at a high standard. This research focuses on the characterization of transmission line matching networks. Different topologies of single-stub and double-stub matching networks will be designed and the frequency of operation, reflection coefficient, insertion loss and bandwidth will be examined. From the designed topologies, physical dimensions of the transmission lines used will be varied and the effects will be examined. Simulations will be done for the design and characterization.